Chapter Adaptive Automation and the Third Pilot - Cahill, Joan (InTechOpen, 2018)
Currently, automation does not take into consideration the cognitive and emotional state of the crew. Rather, automation provides assistance based on explicit and static task assignments, with no adaptive capabilities, even though it is capable of providing higher or lower levels of support depending on the crew state and/or complexity of the operational situation. This chapter presents a new adaptive automation concept which offers an innovative 'team' centred approach to solving crew awareness/workload management problems and enhancing flight safety. Partnership underpins the 'Third Pilot' approach. The crew (pilot flying and pilot monitoring), automation and the 'Third Pilot' are in charge together. Overall, partnership is proposed. This replaces existing paradigms involving dynamic changes in control function, where changes can be autonomously controlled by the system. Moreover, a new multimodal cockpit concept is advanced providing enhanced assessment of crew state/workload.